Delayed Diagnosis of High Drug‐Resistant Microorganisms Carriage in Repatriated Patients: Three Cases in a French Intensive Care Unit. Issue 3 (28th February 2015) - Allyn, Jérôme; Angue, Marion; Belmonte, Olivier; Lugagne, Nathalie; Traversier, Nicolas; Vandroux, David; Lefort, Yannick; Allou, Nicolas
Abstract : We report three cases of high drug‐resistant microorganisms (HDRMO) carriage by patients repatriated from a foreign country. National recommendations suggest systematic screening and contact isolation pending results of admission screening of all patients recently hospitalized abroad. HDRMO carriage (carbapenem‐resistant Acinetobacter baumanii and carbapenemase‐producing Enterobacteriaceae ) was not isolated on admission screening swabs, but later between 3 and 8 days after admission. In absence of cross‐transmission, two hypotheses seem possible: a false‐negative test on admission, or a late onset favored by antibiotic pressure. Prolonged isolation may be discussed even in case of negative screening on admission from high‐risk patients.